2007
DOI: 10.3390/12081964
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Synthesis of 1-(4-Hydroxyiminomethylpyridinium)-3-pyridiniumpropane Dibromide – A New Nerve Agent Reactivator

Abstract: Preparation of 1-(4-hydroxy-iminomethylpyridinium)-3-pyridiniumpropane dibromide is described. This compound represents a new acetylcholinesterase (AChE) reactivator, which has no substituents on the second pyridinium ring as found in other commonly used AChE reactivators. The reactivation ability of this reactivator was tested on tabun-and cyclosarin-inhibited AChE. According to the results obtained, the new compound (without substitution and with decreased molecule size) showed increased reactivation potency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…Recently, the new bispyridinium oximes K156 [1-(4-hydroxyiminomethylpyridinium)-3-pyridiniumpropane dibromide] and K203 [1-(4-carbamoylpyridinium)-4-(4-hydroxyiminomethylpyridini um)-but-2-ene dibromide] (Fig. 1) were primarily synthesized at our department (11,19) to improve the efficacy of antidotal treatment in eliminating tabun-induced acute to- 215 …”
Section: Introductionmentioning
confidence: 99%
“…Recently, the new bispyridinium oximes K156 [1-(4-hydroxyiminomethylpyridinium)-3-pyridiniumpropane dibromide] and K203 [1-(4-carbamoylpyridinium)-4-(4-hydroxyiminomethylpyridini um)-but-2-ene dibromide] (Fig. 1) were primarily synthesized at our department (11,19) to improve the efficacy of antidotal treatment in eliminating tabun-induced acute to- 215 …”
Section: Introductionmentioning
confidence: 99%
“…Currently, strategies for the development of effective oximes can be broadly classified into two categories: the kinetic approach [37,39,[41][42][43] and a structural approach [35,36,38,40] . Kinetics studies on oxime function have revealed that reactivation proceeds via a twostep reaction that consists of the formation of a fully reversible Michaelis-type enzyme-inhibitor-oxime complex followed by the splitting of the complex into a phosphorylated oxime and reactivated enzyme.…”
Section: Wwwchinapharcom Kesharwani Mk Et Almentioning
confidence: 99%
“…Intentional (in a suicidal attempt [28] ) or unintentional (through trace dietary contaminants [29] or through chemical warfare [30] ) OP intoxication is a major threat to human kind. While intoxication by OPs accounts for up to 80% of pesticide-related hospitalization [31] , the possibilities of terrorist attacks (like the Iraqi weaponized sarin attack against the Kurdish [32] or the Tokyo subway sarin attack [33] ) with nerve agents looms large, and thus the discovery of effective OP antidotes is necessary and urgent [34][35][36][37][38][39][40][41][42][43][44][45][46] . Thus, fundamental studies [16,17] elucidating the passage of molecules through the AChE gorge into the active triad of the enzyme is of paramount importance for the discovery of new drugs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the replacement of commonly used oximes (pralidoxime, obidoxime) as well as H-oximes (the oxime HI-6) with a more effective oxime has been a long-standing goal for the treatment of tabun poisoning. For this reason, the new bispyridinium oxime K203 [1-(4-carbamoylpyridinium)-4-(4-hydroxyiminomethylpyridinium)-but-2-ene dibromide] (Figure 1) was synthesized in our department 12,13 and was found to be a promising oxime against tabun poisonings based on the evaluation of its reactivating and therapeutic efficacy against tabun 14 . Unfortunately, the oxime K203, as the other known oximes, especially bispyridinium oximes, has rather low potency to reactivate nerve agent-inhibited AChE in the brain due to its limited penetration across the blood-brain barrier (BBB) 14 .…”
Section: Introductionmentioning
confidence: 99%